Pengaruh Praktikum Berbasis Bahan Alam melalui Model Discovery Learning terhadap Motivasi dan Hasil Belajar Kimia Peserta Didik - Farianti, Dewi; Danial, Muhammad; Aulia, Army (Program Pasca Sarjana UNM, 2020)
The study is quasi experiment research, which aims at examining the extend of the influence of practicum based on natural ingredients through discovery learning model on motivation and learning outcomes in UPT SMAN 9 Maros in Marusu subdistrict in Maros distric of academic year 2018/2019. The total of research population was 143 students with the samples 71 students. Sampling determining technique employed random sampling. Data were collected by using instruments with questionnaire and test. Data were analyzed by using SPSS software. The results of the study reveal (1) the practicum based on natural ingredients through discovery learning model gave positive on chemistry learning motivation in UPT SMAN 9 Maros with the mean percentage of 67.99%, which is in high category, (2) the practicum based on natural ingredients through discovery learning model gave improvement of chemistry learning outcomes in UPT SMAN 9 Maros with the mean percentage of 75.35%, which is in high category. (3) there is significant and positive correlation between motivation and chemistry learning outcomes in UPT SMAN 9 Maros with correlation analysis value of 0.661.